Development of Interactive E-Modules for Literacy Courses in Physics Learning Assisted by Google Sites to Improve Students’ Problem-Solving Skills - Dea Stivani Suherman; Fuja Novitra; Rani Oktavia; Hayyu Yumna; Asrizal (Postgraduate, University of Mataram, 2025)
This study aims to determine the needs analysis, validity, and limited practicality of interactive e-modules assisted by Google Sites to improve problem-solving skills in literacy courses in physics learning. The study adopts a development approach grounded in the Plomp model. The data were then analyzed using descriptive statistical analysis techniques. The needs analysis shows low problem-solving skills and a lack of contextual teaching materials, thus requiring the development of more innovative e-modules. The analysis results also show that the characteristics of the students are in the good category, thus supporting the implementation of these teaching materials. The validity of the developed interactive e-module reached 0.86, indicating that the e-module is valid. The average practicality score was 0.70, which falls into the practical category. These results indicate that the interactive e-module developed is necessary, valid, and practical. These findings confirm that the e-module has met the quality criteria for development, making it suitable for use in learning and ready to proceed to the effectiveness testing stage to assess its potential in improving students' problem-solving skills.